Cyclic di-GMP Regulates the Type III Secretion System and Virulence in Bordetella bronchiseptica - Gutierrez, María de la Paz (2022)
The second messenger cyclic di-GMP (c-di-GMP) is a ubiquitous molecule in bacteria that regulates diverse phenotypes. Among them, motility and biofilm formation are the most studied. Furthermore, c-di-GMP has been suggested to regulate virulence factors, making it important for pathogenesis. Previously, we reported that c-di-GMP regulates biofilm formation and swimming motility in Bordetella bronchiseptica. Here, we present a multi-omics approach for the study of B. bronchiseptica strains expressing different cytoplasmic c-di-GMP levels, including transcriptome sequencing (RNA-seq) and shotgun proteomics with label-free quantification. We detected 64 proteins significantly up- or downregulated in either low or high c-di-GMP levels and 358 genes differentially expressed between strains with high c-di-GMP levels and the wild-type strain. Among them, we found genes for stress-related proteins, genes for nitrogen metabolism enzymes, phage-related genes, and virulence factor genes. Interestingly, we observed that a virulence factor like the type III secretion system (TTSS) was regulated by c-di-GMP. B. bronchiseptica with high c-di-GMP levels showed significantly lower levels of TTSS components like Bsp22, BopN, and Bcr4. These findings were confirmed by independent methods, such as quantitative reverse transcription- PCR (q-RT-PCR) and Western blotting. Higher intracellular levels of c-di-GMP correlated with an impaired capacity to induce cytotoxicity in a eukaryotic cell in vitro and with attenuated virulence in a murine model. This work presents data that support the role that the second messenger c-di-GMP plays in the pathogenesis of Bordetella.